(untitled) (Hekima Review, 2018)
The youth in Africa, do not only hold the key to Africa’s revitalization, but also that of the African Church. So paying attention to their faith and their future should be integral and central to the mission of the Church. In the light of the 2018 Synod on the youth, this paper offers a critical theological reflection on the context of Africa, and proposes some principles that can guide us in building a Church that is truly of and for the youth in Africa.